Two Independent HIV Epidemics in Saint Petersburg, Russia Revealed by Molecular Epidemiology - Dukhovlinova, Elena (AIDS Res Hum Retroviruses, 2015)
The HIV epidemic in Russia, one of the world's fastest growing, has been concentrated mostly among people who inject drugs (PWID). We sought to explore the epidemiology of the epidemic in St. Petersburg by sampling from the highest risk groups of PWID and men who have sex with men (MSM) and use viral sequencing data to better understand the nature of the city's epidemic. Serological testing confirmed an HIV prevalence among PWID in excess of 40%. All but 1 of 110 PWID whose blood samples were tested for genetic diversity were infected by subtype A virus, specifically by the A(FSU) strain. The remaining person was infected with a CRF-06cpx recombinant. Analysis of pairwise genetic distance among all PWID studied revealed an average of 3.1% sequence divergence, suggesting clonal introduction of the A(FSU) strain and/or constraints on sequence divergence. The HIV prevalence was less than 10% among MSM. All 17 sequences from HIV-infected MSM were found to be a clade B virus with a much higher average sequence diversity of 15.7%. These findings suggest two independent epidemics with little overlap between the two highest at-risk populations, which will require different HIV prevention approaches.